2019
DOI: 10.1111/hsc.12745
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cardiometabolic risk markers among ethnic groups in Queensland, Australia

Abstract: Very little is known about the cardiometabolic risk of migrants who settle in Australia.This study investigated differences in cardiometabolic risk markers among ethnic groups attending a tailored healthy lifestyle program in Queensland, Australia; and differences in these markers between those living in Australia for shorter versus longer periods of time. Baseline data collected between October 2014 and June 2017 from the Living Well Multicultural-Lifestyle Modification Program were used.People living in ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(41 reference statements)
0
11
0
1
Order By: Relevance
“…Several international studies [9][10][11] have suggested that Arabic-speaking immigrants (immigrants are people born overseas who have settled in a country permanently) [12] have a higher prevalence of CVD and CVD risk factors compared to many other ethnic groups, including the mainstream cultural group of the countries studied. In Australia, the Arabic-speaking immigrant group, which makes up the fourth largest language group (after English) [13], has a higher prevalence of CVD and recurrent CVD events compared to many other groups living in Australia [8,14,15]. It has been suggested that this may be due to lifestyle factors associated with their countries of origin, including the consumption of a high calorie diet, physical inactivity, and high smoking levels, which often persist in Australia [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several international studies [9][10][11] have suggested that Arabic-speaking immigrants (immigrants are people born overseas who have settled in a country permanently) [12] have a higher prevalence of CVD and CVD risk factors compared to many other ethnic groups, including the mainstream cultural group of the countries studied. In Australia, the Arabic-speaking immigrant group, which makes up the fourth largest language group (after English) [13], has a higher prevalence of CVD and recurrent CVD events compared to many other groups living in Australia [8,14,15]. It has been suggested that this may be due to lifestyle factors associated with their countries of origin, including the consumption of a high calorie diet, physical inactivity, and high smoking levels, which often persist in Australia [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some communities found these behaviours more difficult to sustain (although this was not statistically significant) and this may be due to how culturally significant certain food items are within the diet and/or other social and environmental factors that impact on these behaviours. The variations in cardiometabolic risk and the contributing personal behaviours between ethnic communities have been reported elsewhere 28 …”
Section: Discussionmentioning
confidence: 77%
“…A study among newly arrived Sudanese refugees in Queensland identified that more than half were overweight and obese indicating the need for programmes to prevent excessive weight gain and to reduce risk factors for diabetes and cardiovascular disease 27 . Cardiometabolic risk factors differ significantly between ethnic groups living in Queensland and risk appears to increase for those living in Australia for five or more years 28 . Despite the increased risk of chronic conditions, members of CALD communities are less likely to be proactive in accessing health care and have fewer options available for the implementation of preventative measures 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The duration of residency in Australia, as a representation of acculturation, was self-reported at the beginning of the study. A cut-point of 5 years was used as a previous study showed that cardiometabolic risks of migrants increased within 5 years of settling in Australia (32) . Participants were grouped into a duration of '≤5 years' or '>5 years'.…”
Section: Independent Variablesmentioning
confidence: 99%